A molecular perspective on the limits of life: Enzymes under pressure - Huang, Q.; Tran, K.N.; Rodgers, J.M.; Bartlett, D.H.; Hemley, R.J.; Ichiye, T. (Condensed Matter Physics, 2016)
From a purely operational standpoint, the existence of microbes that can grow under extreme conditions, or "extremophiles", leads to the question of how the molecules making up these microbes can maintain both their structure and function. While microbes that live under extremes of temperature have been heavily studied, those that live under extremes of pressure have been neglected, in part due to the difficulty of collecting samples and performing experiments under the ambient conditions of the microbe. However, thermodynamic arguments imply that the effects of pressure might lead to different organismal solutions than from the effects of temperature. Observationally, some of these solutions might be in the condensed matter properties of the intracellular milieu in addition to genetic modifications of the macromolecules or repair mechanisms for the macromolecules. Here, the effects of pressure on enzymes, which are proteins essential for the growth and reproduction of an organism, and some adaptations against these effects are reviewed and amplified by the results from molecular dynamics simulations. The aim is to provide biological background for soft matter studies of these systems under pressure. З чисто функцiональної точки зору iснування мiкробiв, що можуть рости в екстремальних умовах, чи
“екстремофiлiв”, приводить до питання як молекули, з яких створенi цi мiкроби, можуть пiдтримувати їх
структуру i функцiю. Тодi як мiкроби, що живуть при екстремумах температури, були докладно дослiдженi,
то тi, що живуть при екстремумах тиску, нехтувались, частково через труднощi в збираннi зразкiв та проведеннi експериментiв при нормальних умовах для мiкроба. Однак, термодинамiчнi аргументи передбачають, що ефекти тиску могли б привести до рiзних органiзмових варiантiв нiж ефекти температури.
Очевидно, деякi з варiантiв моли б бути серед властивостей конденсованої речовини у внутрiклiтиннiй
рiдинi на додаток до генних модифiкацiй макромолекул чи вiдновлювальних механiзмiв для макромолекул. В даному оглядi ефекти тиску на ензими, якi є важливими протеїнам для росту i репродукцiї органiзму,
та деякi аргументи проти цих ефектiв аналiзуються та доповнюються результатами моделювання методом молекулярної динамiки. Метою огляду є закласти бiологiчну основу для дослiджень цих систем пiд
тиском з точки зору м’якої речовини.